Previous infection and the risk of ischaemic stroke in Italy: the IN2 study. (2nd December 2014) - Consoli, D.; Vidale, S.; Aguglia, U.; Bassi, P.; Cavallini, A.; Galati, F.; Guidetti, D.; Marcello, N.; Micieli, G.; Pracucci, G.; Rasura, M.; Siniscalchi, A.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose There is an increasing interest in new risk factors for ischaemic stroke. Acute and chronic infections could contribute to different aetiological mechanisms of atherosclerosis that lead to cerebrovascular disease. The aim of this study was to investigate the hypothesis that previous infections and Chlamydia pneumoniae in particular increase the risk of ischaemic stroke in the population. Methods This was a prospective case−control study involving 11 Italian stroke units. Controls were age‐ and sex‐matched with cases, represented by patients admitted to hospital for acute ischaemic stroke. For each participant classical vascular risk factors and previous inflammatory and infectious events up to 1 month before were registered. Blood samples were collected to analyse inflammatory markers and titres of antibodies against C. pneumoniae. Results A total of 1002 participants were included (mean age 69 years) with 749 ischaemic stroke patients. Infections occurred within 1 month previously in 12% of the entire sample with a higher prevalence in the case group (14.4% vs. 3.9%). At multivariate analysis of the seropositivity of IgA antibodies against C. pneumoniae increased the risk of stroke significantly (relative risk 2.121; 95% confidence interval 1.255–3.584) and an early previous infection (up to 7 days before the event) contributed to a rise in probability of acute cerebral ischaemia (relative risk 3.692; 95% confidence interval 1.134–6.875). Conclusions Early previous infections and persistent chronic infection of C. pneumoniae could contribute to increase the risk of ischaemic stroke significantly, in the elderly especially.